Comparison of in situ performance-based tests methods to evaluate moduli of railway embankments - Correia, A. Gomes (2009)
Compaction control based on performance-based test methods has been used recently. These test methods use different load and strain rates as well as boundary conditions requiring the need of calibration and correlation between them. In this paper, correlations are established between the small strain modulus Ev measured from different “in situ” per-formed-based test methods carried on a trial embankment. The Ev modulus was obtained from spot tests, namely, static plate loading test (SPLT), light falling weight deflectometer (LFWD), soil stiffness gauge (SSG), and a continuous test with “Portancemètre” equipment. The SPLT was used as a reference test. The paper describes the experimental plan, presents the theory for each test method, and gives the results and established correlations.